PENGARUH TEKNIK RELAKSASI PERNAFASAN TERHADAP TINGKAT KECEMASAN PASIEN PRE OPERASI DI RUANG MATARAMDI RSUD PROF Dr SOEKANDAR MOJOSARI - Wahyuni, Lutfi (JURNAL KEPERAWATAN SEHAT, 2016)
Operation or surgery require patient to have calm in his condition so that the operation can easily going. One of way to reducing an anxiousness is doing technique of Breathing relaxation. Progressive relaxation is effectively the way of relaxation and reducing level of anxiousness that is the way to taking a rest of body muscles, so that can be followed with relaxation of mental and mind. This research aims to analysis influence of breathing relaxation technique to reducing level of anxiousness at pre operation patient in Mataram Room of RSUD Prof Dr. Soekandar Mojosari. The research Design uses Pre-Experimental design in one subject group. The population of this research is every patient who will have experience of operation in Mataram Room of RSUD Prof Dr. Soekandar Mojosari, in May 2016, using sampling technique of consecutive sampling. Identify anxiousness level of patient of pre operation by using sheet of questionnaire before and after giving of technique of relaxation. Result of research will be tested by using Wilcoxon Signed Rank Test. Results of data analysis using Wilcoxon Signed Rank Test that is founded the significant of probability value is 0,002. The calculate probability value is smaller than the probability value that is specified of α=0.05, so that H0 is rejected. This result indicates that there is influence of giving the breathing relaxation technique to reducing of anxiousness at pre operation patient in Mataram Room of RSUD Prof Dr.Soekandar Mojosari. With giving the breathing relaxation technique can reduces level of anxiousness at pre operation patient, so that can help the patient to prepare his self getting the surgery.Keyword: Breathing Relaxation Technique,Anxiousness,Pre Operation.